Green Economy and Sustainable Finance as Pillars of Indonesia’s Economic Resilience Toward a Developed Nation by 2045 - Wedia Hastuti; Irma Maria Dulame; Daniel Susanto (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
The global shift toward a sustainable economy and finance is essential to address climate change and 21st century uncertainties. While existing studies extensively cover green growth in developed economies, there remains a critical gap in understanding how integrated sustainable finance frameworks specifically catalyze economic transformation in emerging markets like Indonesia, particularly within the context of its 2045 vision. This research addresses this gap by assessing the role of green economy implementation and sustainable finance policies as key pillars in strengthening Indonesia’s economic resilience. Employing a qualitative descriptive approach grounded in a comprehensive review of policy reports, international comparative studies, and recent scientific literature, this study offers a novel synthesis of energy transition, digital transformation, and sustainable financial systems. The research contributes by identifying a strategic roadmap that bridges government policy, private sector participation, and technological innovation to achieve long-term resilience. The findings indicate that green investment, renewable energy, and ESG based financial systems are not merely environmental goals but are fundamental drivers of economic stability and national competitiveness. Furthermore, this study demonstrates how sustainable funding tools, such as green bonds and climate finance, can accelerate socio-economically inclusive growth while reducing carbon intensity. The study concludes that the synergy between institutional frameworks and innovative human capital development is the primary determinant of Indonesia’s capacity to achieve sustainable prosperity and reach developed nation status by 2045.